Initial Treatment Patterns and Survival Outcomes of Mantle Cell Lymphoma Patients Managed at Chinese Academic Centers in the Rituximab Era: A Real-World Study - Wu, Meng; Li, Yun; Huang, Huiqiang; Xu, Wei; Wang, Yanyan; Huang, Haiwen; Zhao, Weili; Liu, Shuo; Xu, Pengpeng; Chen, Zhengming; Zhu, Jun; Song, Yuqin; et al. (Frontiers in Oncology, 2022)
Purpose The aim of the study was to delineate the disease characteristics, the initial treatment patterns, and survival in patients with mantle cell lymphoma (MCL) managed in the real world. Methods Data of 518 MCL patients from 5 major Chinese Hematology Centers in the period from 2007 to 2017 were retrospectively analyzed. Results The median age was 58 years. Of the patients, 88.6% had Eastern Cooperative Oncology Group Performance Status (ECOG PS) 0–1 and 80.7% had advanced-stage disease. Ki67 expression was <30% in 39.6% of the patients, and 43.2% of patients were categorized into a low-risk group based on the Mantle Cell Lymphoma International Prognostic Index (MIPI) scoring system. Overall, 73.4% of the patients received rituximab as their first-line therapy. The most commonly used chemotherapy was the CHOP-like (cyclophosphamide, hydroxydaunomycin, oncovin, and prednisone) regimen (45.2%), followed by high-dose cytarabine-containing chemotherapy (31.3%) and bendamustine (3.3%). Of the patients, 13.7% (n = 71) underwent consolidative autologous stem cell transplantation (ASCT), and 19.3% (n = 100) received novel agents containing first-line regimens. With a median follow-up time of 52 months, the 3- and 5-year overall survival (OS) rates were 73.7% and 61.4%, respectively. Age ≤60 years, ECOG PS 0–1, stages I–II, normal lactate dehydrogenase (LDH), absence of bone marrow involvement, Ki67 <30%, and lower-risk IPI/MIPI scores were significantly associated with improved OS (p < 0.05). The inclusion of rituximab improved the 5-year OS, with borderline significance (62.5% vs. 55.2%, p = 0.076). High-dose cytarabine-containing chemotherapy showed significant clinical benefit in 5-year OS (72.1% vs. 55.9%, p = 0.010). Patients with ASCT had better 5-year OS in the younger (≤60 years) age group (87.2% vs. 64.8%, p = 0.002). Conclusion This large retrospective dataset unequivocally confirmed the survival advantage afforded by cytarabine-containing regimen and ASCT in a first-line setting under real-world management in the rituximab era.